The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/s19214676
|View full text |Cite
|
Sign up to set email alerts
|

Design of a 900 MHz Dual-Mode SWIPT for Low-Power IoT Devices

Abstract: This paper presents a duty cycle-based, dual-mode simultaneous wireless information and power transceiver (SWIPT) for Internet of Things (IoT) devices in which a sensor node monitors the received power and adaptively controls the single-tone or multitone communication mode. An adaptive power-splitting (PS) ratio control scheme distributes the received radio frequency (RF) energy between the energy harvesting (EH) path and the information decoding (ID) path. The proposed SWIPT enables the self-powering of an ID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Thus, data rates of 16, 32, and 256 kbps are to be achieved by increasing the digital clock by 64 kHz, 128 kHz, and 1 MHz, respectively. The proposed design of SWIPT is compared with PCB-based SWIPT implementation [36] in Table 1. ASIC-based SWIPT design consumes very low power and area which is desirable for SWIPT operation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, data rates of 16, 32, and 256 kbps are to be achieved by increasing the digital clock by 64 kHz, 128 kHz, and 1 MHz, respectively. The proposed design of SWIPT is compared with PCB-based SWIPT implementation [36] in Table 1. ASIC-based SWIPT design consumes very low power and area which is desirable for SWIPT operation.…”
Section: Resultsmentioning
confidence: 99%
“…As it updates the duty ratio in every frame, it then makes it less efficient. In [ 36 ], a design of duty cycle-based dual mode SWIPT receiver is presented. It is the PCB-based implementation of SWIPT with commercial devices which is not optimized for SWIPT operation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, new SWIPT receiver has to be designed as proposed in refs. [32][33][34] to extend SWIPT in a multi-hop wireless network.…”
Section: Related Workmentioning
confidence: 99%
“…Multitone SWIPT can be realized by arranging the amplitudes, frequencies, phases of each tone or by varying the number of tones [11], [16]- [19]. Among these methods, modulation based on the number of tones is one of the attractive approaches in that it uses PAPR fluctuations by varying the number of tones in the transmitted waveform [20], [21]. These authors revealed the tradeoff between the communication rate and the direct current (DC) supply capability.…”
Section: Introductionmentioning
confidence: 99%